PENERAPAN METODE TALAQQI DALAM MENINGKATKAN KEAKTIFAN SISWA PADA MATA PELAJARAN BAHASA ARAB KELAS VIII A DI MTS BABUSSALAM SIMANDOLAK KECAMATAN BENAI - Desi Susanti; Zulhaini Zulhaini; A Mualif (Universitas Islam Kuantan Singingi, 2022)
Application of the talaqqi method in increasing student activeness in Arabic class VIII A at MTs Babussalam Simandolak, Benai District. Applying learning methods in the learning process is a very easy way to achieve learning objectives. In addition, for the success of the teaching and learning process,it is necessary to pay attention to the method used, so that material delivered is more easily absorbed or captured by students. The learning method used by the teacher must start from a successful and efficient leraning goal because the learning method is basically a plan to achieve the goal. The objectives of this study are to find out how the application of the talaqqi method in improving student activeness in Arabic class VIII A as a subject at MTs Babussalam Simandolak Benai District. Based on the results of research data analysis An author about the application of the talaqqi method in improving student activeness in Arabic class VIII A as a subject at MTs Babussalam Simandolak Benai District. The author conclude that based on before the action until cycle II experienced a significant increase. Before action is 37,6 %,then in the first cycle there was increase with the percentage of 61,6% in the second cycle of 88,8%. The results showed that all aspects of the research increased the application of the talaqqi method in improving student activeness in Arabic class VIII A as a subject at MTs Babussalam Simandolak Benai District experienced an increase in each meeting.